Avoiding Arterial Hypotension in Preterm Neonates (AHIP)—A Single Center Randomised Controlled Study Investigating Simultaneous Near Infrared Spectroscopy Measurements of Cerebral and Peripheral Regional Tissue Oxygenation and Dedicated Interventions - Pichler, Gerhard; Höller, Nina; Baik-Schneditz, Nariae; Schwaberger, Bernhard; Mileder, Lukas; Stadler, Jasmin; Avian, Alexander; Pansy, Jasmin; Urlesberger, Berndt (Frontiers in Pediatrics, 2018)
Introduction: Up to 50% of preterm infants admitted to intensive care units require cardio-circulatory support. The aim of the present study was to assess whether simultaneous monitoring of cerebral (cTOI) and peripheral tissue oxygenation index (pTOI) using near-infrared spectroscopy (NIRS) in combination with dedicated intervention guidelines may help avoiding arterial hypotension and catecholamine administration in preterm neonates. Study design: Preterm neonates <37 weeks of gestation were included in a single center randomised controlled study. Blood pressure was measured non-invasively or invasively. In the NIRS group simultaneous cTOI and pTOI monitoring was used starting within six hours after birth for 24 hours to calculate changes in cTOI/pTOI ratio over time. Depending on these changes, interventions including echocardiography, administration of volume or patent ductus arteriosus (PDA) treatment were performed. In the control group, only routine monitoring and treatment were performed and NIRS signals were not visible. The primary outcome was burden of hypotension within 48 hours after initiation of NIRS monitoring. Results: 49 preterm neonates were included in each group: NIRS group 33.1 (32.0–34.0) [Median: 25-75 centile] weeks of gestation and control group 33.4 (32.3–34.3) weeks of gestation. In the NIRS group echocardiography was performed in 17 preterm neonates due to NIRS measurements, whereby six neonates received further treatment. Percentage of neonates with any hypotensive episode during the 48-hours observational period was 32.6% in the NIRS group and 44.9% in the control group (p=0.214). Burden of hypotension (i.e. %mmHg of mean arterial pressure < gestational age) was 0.0 (0.0–2.1) mmHg-hours in the NIRS group and 0.4 (0.0–3.3) mmHg-hours in the control group (p=0.313), with observed burden of hypotension being low in both groups. No severe adverse reactions were observed. Conclusion: In preterm neonates using simultaneous peripheral and cerebral NIRS measurements for early detection of centralisation followed by predefined interventions led to a non-significant reduction in burden of arterial hypotension. ClinicalTrials.gov Identifier: NCT01910467